Empowerment of writing through creativity - Samame Llanos, María José (2023)
Written competence is fundamental for the individual, since it enables him or her to develop interpersonal, academic and work-related skills. However, there are different factors that can affect its correct acquisition. Therefore, this research has been carried out with the objective of constructing a didactic proposal based on Guilford's theory of divergent thinking to strengthen the production of narrative texts in first grade high school students of the I.E. San Francisco de Lagunas. This work has a quantitative approach, non-experimental and descriptive-qualitative design. The technique is observation and the instrument is the descriptive scale. According to the results, 100% of the students are in the levels of insufficient and not achieved. Finally, it is necessary that teachers take action and through this program contribute to the improvement of writing through creative thinking.